The fine-needle aspiration cytology and clinical findings of Kikuchi–Fujimoto disease in pediatric patients: a retrospective clinical study. (1st April 2022) - Naoi, Yuto; Tachibana, Tomoyasu; Wani, Yoji; Hotta, Machiko; Haruna, Katsuya; Komatsubara, Yasutoshi; Kuroda, Kazunori; Fushimi, Soichiro; Nagatani, Tami; Kataoka, Yuko; Nishizaki, Kazunori; Sato, Yasuharu; et al.
Abstract: Background: Histological evaluation of lymph node is crucial for the definitive diagnosis of Kikuchi–Fujimoto disease (KFD). However, lymph node biopsy under local anesthesia is often difficult in pediatric patients. Objectives: We evaluated cytological findings for pediatric patients with prolonged cervical lymphadenitis clinically suggestive of KFD and investigated the clinical characteristics of patients diagnosed with KFD by fine-needle aspiration cytology (FNAC). Methods: This retrospective clinical study included 58 Japanese pediatric patients with cervical lymphadenitis who underwent FNAC. Results: Cytological diagnosis was KFD for 22 and suspicion of KFD for 11 patients. The remaining 25 patients were diagnosed with non-specific lymphadenitis (NSL). Tenderness was independently associated with a higher frequency of both KFD in narrow and broad senses, compared with NSL ( p = .009; p = .038). The percentage of patients who underwent FNAC within 28 days from symptom onset tended to be higher among patients with KFD in a narrow sense than those with NSL ( p = .052). Conclusion: This study indicated that the period from symptom onset to FNAC (<28 days) and the symptom of tenderness were associated with the cytological diagnosis of KFD.